THE ASYMMETRY OF INFORMATION ON FOOD MARKET AND CONSUMERS’ PREFERENCES – SOME ASPECTS - Renata Nestorowicz (Polityki Europejskie, Finanse i Marketing)
There is the asymmetry of information between the subjects that represent supply and demand on food market. The level of the asymmetry is differentiated depending on a product category. The following paper focuses on bioactive/functional food. These are segments in which the asymmetry is particularly visible as the characteristics of these food products (especially prohealth characteristics) may be revealed only after consumption. The discussion indicates interrelations between the level of consumers’ knowledge and the level of the asymmetry of information on food market of functional/bioactive products. The influence of the asymmetry of knowledge and the asymmetry of information on consumers preferences has been presented based on the results of the conducted research.